On the Effects of Fiscal and Monetary Policy: A Taxonomic Discussion - Hansen, Bent (American Economic Review, 2016)
Current debate on monetary and fiscal policies is much concerned with the effects of such policies, and of changes in the budget and money supply. I propose here to discuss some taxonomic problems related to the concept of policy effects. Their resolution bears directly upon the controversy between Keynesians and Monetarists. I shall show that it is largely a sham-dispute, and it will appear that the empirical findings of the Monetarists have little relation to the Keynesian creed. Even negative effects of the budget with strong positive effects of money supply are fully consistent with strong positive effects of fiscal action and weak or strong effects of monetary action. The examination of the concept of effects of economic policy will be undertaken in relation to a model that is specified so as to include both the conventional Keynesian set-up for determining effective demand, and a credit mechanism that links effective demand to the banking system in the spirit of the Monetarists